Comparison of cardiopulmonary responses of male and female rats to intermittent high altitude hypoxia - Ostádal, B; Procházka, J; Pelouch, V; Urbanová, D; Widimský, J (Physiologia Bohemoslovaca, 1984)
Intermittent high altitude hypoxia (8 hours a day, 5 days a week, stepwise up to the altitude of 7000 m, total number of exposures 24) induced in male and female rats, chronic pulmonary hypertension and right ventricular hypertrophy. No significant sex differences were found in both these parameters. A significant sex difference was demonstrated in the resistance of the cardiac muscle to acute anoxia in vitro: the myocardium of control female rats proved to be significantly more resistant to oxygen deficiency. Intermittent altitude hypoxia resulted in significantly enhanced resistance in both sexes, yet the sex difference was maintained. Sex differences were further observed in the growth response of experimental animals to the acclimatization process. Whereas the body weight of male rats exposed to intermittent altitude hypoxia was significantly lower, hypoxic females had body weights comparable to those of control animals.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Glycogen; Rats; hypoxie; Cardiomegaly; Hypoxia; Myocardial Contraction; sexuální faktory; Hypertension, Pulmonary; mužské pohlaví; kardiomegalie; Hemoglobins; krysa rodu Rattus; Body Weight; glykogen; ženské pohlaví; plicní hypertenze; myokard; zvířata; Hemodynamics; Altitude; Sex Factors; Myocardium; tělesná hmotnost; hemodynamika; hemoglobiny; nadmořská výška; kontrakce myokardu; Female; Male; Animals